Secondary Capital Market of Nepal: Assessing the Relationship Between Share Transaction and NEPSE Index - Chalise, Dhan Raj (Management Dynamics, 2020)
Capital Market plays a significant role in financial mobilization and provide an effective way of procuring long-term funds at same. In a addition it provide an investment opportunity for individuals and institutions. Nepalese capital market is growing and improving phase. The objective of this study is to assess the existing status of secondary capital market and to examine the relation between the share transaction amount and NEPSE Index. The period 2009/10 to 2018/19 has been used for study purpose. The trends of capital market development track after 2009/10 to present status has been indentified using descriptive analytical research design. Applying secondary data, the results found that there has significant contribution of secondary capital market for financial resources mobilization in Nepal. In addition, there exist significant positive impact of share transactions on NEPSE Index in Nepalese secondary capital market. The study recommends more effort form related sector for the modernization and systematization of share market.